2005
DOI: 10.1146/annurev.psych.56.091103.070225
|View full text |Cite
|
Sign up to set email alerts
|

Brain Organization for Music Processing

Abstract: Research on how the brain processes music is emerging as a rich and stimulating area of investigation of perception, memory, emotion, and performance. Results emanating from both lesion studies and neuroimaging techniques are reviewed and integrated for each of these musical functions. We focus our attention on the common core of musical abilities shared by musicians and nonmusicians alike. Hence, the effect of musical training on brain plasticity is examined in a separate section, after a review of the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
427
0
52

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 648 publications
(519 citation statements)
references
References 191 publications
19
427
0
52
Order By: Relevance
“…A long history of dissociation between aphasia and amusia from the clinical neurology suggested that there are differences in the ways music and language are implemented by the brain, and modern brain imaging work has partially confirmed this finding. To the extent that music really requires a different suite of mechanisms from language, this is prima facie evidence against its being a spandrel of language (Peretz & Hyde, 2003;Peretz & Zatorre, 2005) but the considerable overlap between brain regions involved in musical and lingustic tasks currently offers no clear verdict on this question at present (Koelsch et al, 2002(Koelsch et al, , 2004Patel, 2003;Peretz & Zatorre, 2003). Another approach is to seek evidence that musical and linguistic skills are dissociated among individuals in a population, and that these differences have a genetic basis.…”
Section: Music As a Spandrelmentioning
confidence: 99%
“…A long history of dissociation between aphasia and amusia from the clinical neurology suggested that there are differences in the ways music and language are implemented by the brain, and modern brain imaging work has partially confirmed this finding. To the extent that music really requires a different suite of mechanisms from language, this is prima facie evidence against its being a spandrel of language (Peretz & Hyde, 2003;Peretz & Zatorre, 2005) but the considerable overlap between brain regions involved in musical and lingustic tasks currently offers no clear verdict on this question at present (Koelsch et al, 2002(Koelsch et al, , 2004Patel, 2003;Peretz & Zatorre, 2003). Another approach is to seek evidence that musical and linguistic skills are dissociated among individuals in a population, and that these differences have a genetic basis.…”
Section: Music As a Spandrelmentioning
confidence: 99%
“…Advances in neuroimaging technology and methods have underpinned extensive study of musicians over the past decade (Peretz and Zatorre, 2005). On the one hand, coarse anatomical plastic changes have been observed using in-vivo magnetic resonance morphometry and voxel-based morphometry (VBM) (e.g.…”
mentioning
confidence: 99%
“…Os sons musicais e todos os outros sons compartilham a maioria das etapas de transformação ao longo do eixo neural auditivo (Peretz & Zatorre, 2005). Por esta razão é necessário que o sistema auditivo integre os sons sequencialmente.…”
unclassified
“…O processo de desempenho musical se realiza visual e auditivamente e possui feedback de integração somatossensorial (Lotze, Scheler, Tan, Braun, & Birbaumer, 2003). Além desses processos, os músicos devem diferenciar sequências organizadas acusticamente como números de signos limitados, com regras especiais e suas infinitas possibilidades de combinação, por isso a contribuição da memó-ria operacional para o processamento musical é crucial (Peretz & Zatorre, 2005;Rauscher & Zupan, 2000;Sallat & Stachowiak, 2005).…”
unclassified